The comparison between modeling of edge localized modes with a current relaxation model and experiment on EAST - Cai, J Q; Liang, Y; Pearson, J; Zhang, T; Zang, Q; Wu, M Q; Huang, J (Plasma physics and controlled fusion, 2017)
The distinctions of edge localized mode (ELM) frequency distributions between moderate and high edge current density cases were observed on the experiment advanced superconducting tokamak. In this paper, a current relaxation model is applied to explain this new observation. It has been demonstrated that the ELM frequency is very sensitive to the edge current density and the edge safety factor by the model predictions. The results also show that, in the large edge current density case, the ELM frequency is subject to a single-peak distribution; while in the moderate edge current density case, the ELM frequency is subject to a roughly multi-peak distribution.